2018
DOI: 10.3390/su10113827
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reduced Protein Content in Complete Diets with a Consistent Arginine–Lysine Ratio on Performance and Nitrogen Excretion in Broilers

Abstract: The current discussion concerning resource-efficient broiler production inevitably leads to diets with lowered crude protein (CP) levels. Therefore, the hypothesis was formed that crude protein reduction far below the recommended levels can significantly lower the nitrogen (N) content in litter, if essential amino acids are added and a constant lysine-arginine ratio is guaranteed. In a five-week feeding trial, 360 ROSS 308 broilers of both sexes were randomly assigned to four feeding groups with six replicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…The N-retention efficiency was increased by about 12.6% by feeding SFI-Corn diets than those fed the control diet due to adding the crushed corn to the pellets. The present data are in line with the results of Ullrich et al [29], who were able to reduce the N-content in the final litter by about 28.4% by reducing the protein content intentionally in the starter, grower and finisher diets (192, 177 and 170 g/kg DM, respectively). Ospina-Rojas et al [58] found a reduction in the N-content in the litter of about 32.4% when reducing the level of protein in the diet from 19% to 16% intentionally with a constant performance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The N-retention efficiency was increased by about 12.6% by feeding SFI-Corn diets than those fed the control diet due to adding the crushed corn to the pellets. The present data are in line with the results of Ullrich et al [29], who were able to reduce the N-content in the final litter by about 28.4% by reducing the protein content intentionally in the starter, grower and finisher diets (192, 177 and 170 g/kg DM, respectively). Ospina-Rojas et al [58] found a reduction in the N-content in the litter of about 32.4% when reducing the level of protein in the diet from 19% to 16% intentionally with a constant performance.…”
Section: Discussionsupporting
confidence: 93%
“…For estimating the efficiency of nitrogen intake, all pens were used as an observation unit for evaluating nutrient efficiency between groups. The basis for consideration was the total feed intake in the pen, the body weight gain and the amount of final litter in the pen in accordance with Ullrich et al [29]. Briefly, to calculate the N-content in the fresh whole body of birds (including feathers), crude protein levels from previous publications were used [30,31].…”
Section: Estimation Of Nitrogen Efficiencymentioning
confidence: 99%
“…Each percent reduction of protein in the diet reduced 10% of the N excretion [36]. Our study confirmed that a reduced protein diet reduced nitrogen excretion, which is in agreement with the reduction of nitrogen emissions in feces [19,31,32,[36][37][38].…”
Section: Nitrogen Digestibilitysupporting
confidence: 88%
“…The present study concentrated, besides the protein reduction in feed, which was already successful in a first trial (protein reduction by 2%; [6]), now on the optimization of the amino acid supply of broilers. More precisely, on the effectiveness of the various Met sources, it is the first limiting AA [7,8] and of great relevance to birds.…”
Section: Introductionmentioning
confidence: 99%